2017
DOI: 10.1186/s13568-017-0467-1
|View full text |Cite
|
Sign up to set email alerts
|

NAD+-dependent HDAC inhibitor stimulates Monascus pigment production but inhibit citrinin

Abstract: Monascus species are edible fungi due to the production of food colorant and other beneficial compounds. Hence, it has been an attractive thesis to improve their productivities. Increasing numbers of investigations revealed that regulating the activities of histone deacetylases can significantly perturb secondary metabolites (SM) production at a global level. In this study, dihydrocoumarin (DHC, an inhibitor of the Sirtuin family of NAD+-dependent deacetylases) was used to treat Monascus ruber for evaluating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…To remove citrinin from Monascus products, several methods, screened for low or no production of citrinin from Monascus strains and a lack of mutagenesis and gene transformation of Monascus, have been developed in the last several decades. [22][23][24][25][26][27] In our previous study, we found that some flavonoids can affect the production of citrinin by Monascus. 28 Soybean isoflavones (SI) are flavonoids whose main components include daidzein, genistein, soybean flavin, and flavin glycoside.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…To remove citrinin from Monascus products, several methods, screened for low or no production of citrinin from Monascus strains and a lack of mutagenesis and gene transformation of Monascus, have been developed in the last several decades. [22][23][24][25][26][27] In our previous study, we found that some flavonoids can affect the production of citrinin by Monascus. 28 Soybean isoflavones (SI) are flavonoids whose main components include daidzein, genistein, soybean flavin, and flavin glycoside.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, methods to reduce the citrinin content of Monascus products have attracted great attention in Monascus ‐related research. To remove citrinin from Monascus products, several methods, screened for low or no production of citrinin from Monascus strains and a lack of mutagenesis and gene transformation of Monascus , have been developed in the last several decades …”
Section: Introductionmentioning
confidence: 99%
“…CRI7 33 Cytotoxic (A549: 46.5 mg mL À1 , HuCCA-1: 48.1 mg mL À1 , MOLT-3: 17.4 mg mL À1 ) Dothideomynones B (39), D-F (41)(42)(43) Dothideomycete sp. CRI7 34 Mycoleptone A (44) Mycoleptodiscus indicus 15 Cytotoxic (PC3: 10.0 mM); antileishmanial (Leishmania major: 28.5 mM) Mycoleptone B (45) Mycoleptodiscus indicus 15 Cytotoxic (PC3: 7.1 mM); antileishmanial (Leishmania major: 21.7 mM) Mycoleptone C (46) Mycoleptodiscus indicus 15 Deectin C1 (47) Aspergillus deectus NCC0415 36 Inhibit enzyme (SHP2: 29.3 mM, PTP1B: 40.4 mM) Deectin C2 (48) Aspergillus deectus NCC0415 36 Inhibit enzyme (SHP2: 21.1 mM, PTP1B: 19.8 mM) Deectin C3 (49) Aspergillus deectus NCC0415 36 Inhibit enzyme (SHP2: 16.2 mM, PTP1B: 16.5 mM) (51) Aspergillus deectus NCC0415 36 Inhibit enzyme (SHP2: 7.0 mM, PTP1B: 6.1 mM) Deectin E (52) Aspergillus deectus NCC0415 36 Inhibit enzyme (SHP2: 16.0 mM, PTP1B: 24.0 mM) 8,11-Didehydrochermesinone B (53) Nigrospora sp. YE3033 26 Colletotrichone A (54) Colletotrichum sp.…”
Section: Species Activitymentioning
confidence: 99%
“…This subgroup including thirteen compounds were characterized by an angular lactone on the azaphilone nucleus with a propenyl side chain and an acyl chain ( Fig. 6 and Table 1), for example, monascuskaodione (82), 44 monascuspurone (83), 45 monasuol B (84), 46 acetyl-monasuol B (86), 47 MC-2 (87), and MC-4 (88). 48 Monascusazaphilone C (85), carrying with an acetoxy group attached at the side chain, was obtained from Monascus purpureus BCRC 38108, which showed moderate NO inhibitory activity (IC 50 ¼ 6.8 mg mL À1 ).…”
Section: Angular Lactone-type Azaphilonesmentioning
confidence: 99%
See 1 more Smart Citation